Posesti krške škofije na področju današnje slovenske Štajerske v drugi polovici 13. stoletja - Bele, Martin (Studia Historica Slovenica, 2016)
The article discusses the origin, history, politics and estates of the diocese of Gurk. It focuses on the period from 1043 to the end of the 13th century and the then estates of the diocese of Gurk in the present-day Slovenian Styria. It is divided into two parts; the first roughly covers the period between 1043 and 1232 (when the dioceses of Salzburg and Gurk came to a permanent settlement in the election and appointment of the bishops of Gurk), and the second the remainder of the 13th century. Both parts analyse the estate structure of the diocese of Gurk, the family ties of the then ministeriales of Gurk, their political and military activities, and the political and military activities of the then bishops of the diocese of Gurk. They are written on the basis of the published sources and professional literature in the field of Slovenian, Austrian and Croatian medieval history.
Keywords: Avstrija; gradovi; Krška škofija; lastnina; nepremičnine; Slovenija; upravljanje; zemljiška posest